ENHANCING PRESENTATION ABILITIES IN STUDENTS VIA INFOGRAPHICS WITHIN THE EMANCIPATED CURRICULUM FRAMEWORK - Fatmawati, Riska; Widiyati, Elok (University of Kuningan, 2024)
Abstract: Presentation is a part of applying speaking skill. One of the media which be used in presentation activities is infographics. The purpose of this study was to determine the effect of using infographics on students' ability in presentation skill. This research was quantitative and used the quasi-experimental design. The data was taken from the pre-test and the post-test of presentation by applying project-based learning. It was conducted in class XI MA Roudlotul Muttaqin, Demak with a total of 50 students. There were two classes involved in this study, they were the experimental class and the control class. The experimental class received the treatment in the form of infographics, while the control class was not. In this study, the researchers collected data in three steps, they were the tryout for the non-sample class, the pre-test, and the post-test. The average tryout in the non-sample class was 82.75. The average pre-test in the experimental class was 79.75, while the average pre-test in the control class was 78.00. The average post-test in the experimental class was 91.5, while the average post-test in the control group was 85.25. The results of the T-test data value Sig. (2 tailed) was lower than 0.05, in the pre-test and the post-test results. It can be concluded H1 was accepted and H0 was rejected, showing the use of infographic media was effective to improve students' presentation skills.